The Prospect of Zakat Growth in Indonesia and its Effect on Economic Growth in Indonesia (UIN Sunan Kudus, 2024)
The Zakat institutions have commenced improving organizational governance, leading to the ease of the Zakat payment, while people's awareness of paying Zakat has increased lately. This study aims to forecast Zakat growth over the next 10 years and test its growth against national economic growth in Indonesia. This study used secondary data that is time-series. Using regression analysis, the Autoregressive Integrated Moving Average (ARIMA) was used to estimate Zakat growth over the upcoming decade and examine the relationship between Zakat and economics. The results of this study have showed that the average growth of Zakat for a decade would reach 10%, doubling that of Infaq and Alms receipts. It discloses that Zakat in Indonesia is found to grow more quickly compared to the other forms of charitable giving over the same time period. Moreover, the growth of Zakat receipts has been found to have a positive effect on national economic growth, indicating that Zakat distributed across Indonesia encourages economic growth in Indonesia.